2019
DOI: 10.1111/cen.14046
|View full text |Cite
|
Sign up to set email alerts
|

How do paediatricians use and monitor antithyroid drugs in the UK? A clinician survey

Abstract: Objective We aimed to document current practice in the medical management of paediatric hyperthyroidism in the UK and compare to international recommendations. Design A 27‐question online survey distributed via an electronic newsletter in August 2018. Participants Responses from 48 members (11%) of the British Society for Paediatric Endocrinology and Diabetes. Measurements Information about antithyroid drug (ATD) preference, treatment duration, monitoring of full blood count (FBC), management of neutropaenia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A key underlying premise for those who advocate BR is that it is easier to replace thyroxine in an appropriate quantity in the 'blocked' Graves' patient than it is to adjust the ATD dose in a way that renders the hyperthyroid patient euthyroid. The American Thyroid Association guideline that recommend the DT strategy does so on the basis that the likelihood of side effects is reduced [28,29] but some clinicians continue to feel that biochemical stability is better with BR [30] and this strategy is still used regularly by paediatricians in the UK [31,32]. The potential benefits of one approach versus the other may be different in childhood because the underlying disease tends to be more severe and because the young, growing person is changing in size with an associated change in thyroid hormone requirement.…”
Section: Block and Replace Or Dose Titration Atdmentioning
confidence: 99%
“…A key underlying premise for those who advocate BR is that it is easier to replace thyroxine in an appropriate quantity in the 'blocked' Graves' patient than it is to adjust the ATD dose in a way that renders the hyperthyroid patient euthyroid. The American Thyroid Association guideline that recommend the DT strategy does so on the basis that the likelihood of side effects is reduced [28,29] but some clinicians continue to feel that biochemical stability is better with BR [30] and this strategy is still used regularly by paediatricians in the UK [31,32]. The potential benefits of one approach versus the other may be different in childhood because the underlying disease tends to be more severe and because the young, growing person is changing in size with an associated change in thyroid hormone requirement.…”
Section: Block and Replace Or Dose Titration Atdmentioning
confidence: 99%
“…A recent audit suggested improved biochemical control in paediatric patients managed with BR but patient numbers were small and individuals managed with BR had been on ATD for longer (22). Paediatric endocrinologists in the UK still use the BR strategy (23) which may indicate that some clinicians feel that BR is a useful strategy in selected patients where DT does not result in biochemical stability.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 2016 ATA guidelines recommended against the use of BR regimens based on these findings [8], they continue to be utilized in clinical practice, particularly for patients who experience fluctuations in thyroid function with only minimal changes in MMZ dosage. A 2018 survey in the UK revealed that BR regimens were still commonly used among pediatric endocrinologists, with 29% favoring BR compared to 65% using DT [21].…”
Section: Main Textmentioning
confidence: 99%